Numerical solution of linear volterra integral equation - Souida, Hanene; Dilmi, Mustapha: Encadreur (Mohamed Boudiaf University of M'sila, 2019)
The main objective of this work is to study the integrale equation particulary the linear volterra integral equations and resolve them whith di§rent ways(analytical :Degenerate core...,numerical :Galerkin,...)
Keywords: Integral equation; projection method; collocation method; Galerkin method; Orthogonal polynomials